Association between IL-1RN VNTR, IL-1 beta -511 and IL-6 (-174, -572, -597) Gene Polymorphisms and Urolithiasis - Çoker Gürkan, Ajda; Palavan Unsal, Narçin; Arısan, Serdar; Sonmez, Nurettin Cem; ARISAN, ELİF DAMLA (Karger, Allschwilerstrasse 10, Ch-4009 Basel, Switzerland, 2013)
Urolithiasis is a common multifactorial urological disorder that is characterized by stone formation. Interleukin (IL)-1 and IL-6 are pro-inflammatory cytokines that might be linked with urolithiasis. The single nucleotide polymorphisms within the IL-1 and IL-6 cytokine genes altered the cytokine expression levels. Our aim was to investigate the potential of IL-1 beta (-511 C>T), IL-6 (-174 G>C, 572 G>C, 597 G>A) and IL-1 RN VNTR gene polymorphisms to be a genetic marker for urinary stone disease. The polymorphisms studied in the promoter regions of IL-1 beta and IL-6 genes did not reveal a strong association with urolithiasis when compared to the control group (p = 0.293, 0.871, 0.921, 0.536, respectively). However, a significant difference was observed between control and patient groups for IL-1 RN VNTR gene polymorphism (chi(2) = 6.131, d.f. = 2, p = 0.047). Our data provide evidence that IL-1RN VNTR gene polymorphism may be involved in the pathogenesis of urinary stone formation, contributing to genetic susceptibility for urolithiasis. (C) 2013 S. Karger AG, Basel
Keywords: Urolithiasis; Interleukin-1; Interleukin-6; Single nucleotide polymorphism; Receptor Antagonist Gene; Calcium-Oxalate Stones; Vitamin-D-Receptor; Kidney-Stones; Interleukin-1-Beta Gene; Tandem Repeat; Nephrolithiasis; Excretion; Intron-2; Protein